Structural Intervention Time Series Analysis of Crime Rates: The Impact of Sentence Reform in Virginia - Suncica Vujic; Jacques Commandeur; Siem Jan Koopman (Tinbergen Institute, 2012)
We adopt a structural time series analysis to investigate the impact of parole abolition and sentence reform in Virginia on reported crime rates. The Commonwealth of Virginia abolished parole and reformed sentencing for all felony offences committed on or after January 1, 1995. To examine the impact of Virginia's change in legislation on reported crime rates from 1995 onwards, we perform an intervention time series analysis based on structural time series models. We empirically find that the change in legislation has significantly reduced the burglary rates and to a lesser extent the murder rates in Virginia. For other violent crimes such as rape and aggravated assault the evidence of a significant reduction in crime rates is less evident or is not found. This empirical study for Virginia also provides an illustration of how an effective intervention time series analysis can be carried out in crime studies.
urn:NBN:nl:ui:31-1871/38494
Keywords: C22; C32; I28; K14; 330; Intervention time series analysis; Crime rates; Structural time series models; Unobserved components time series models; Kriminalität; Staatliche Information; Zeitreihenanalyse; Virginia